Assessment Syrian Population Knowledge, Attitudes and Perceptions Towards Stroke: A Cross-Sectional Study from Syria - Yazan Khair Eldien Jabban; Sarya Swed; Haidara Bohsas; Hidar Alibrahim; Nagham Jawish; Bisher Sawaf; Wael Hafez (University Library System, University of Pittsburgh, 2022)
Background: Based on the stroke mortality rate, Syria was ranked 98th worldwide in 2020. Approximately 80% of strokes are avoidable by managing well-known modifiable risk factors, such as diabetes, hypertension, and cardiovascular disease. Due to the high prevalence of several modifiable risk factors for stroke in Syria, it is necessary to increase Syrians' understanding of strokes and encourage people to engage in healthy practices to eradicate these risk factors. This research aimed to evaluate the knowledge, attitudes, and health-related perceptions of adult Syrians about stroke.   Methods: This cross-sectional research was conducted between 2 September and 10 October 2022 among Syrians using an online survey to measure their knowledge, attitudes, and practices regarding stroke. This questionnaire was derived from a previously published article, and the inclusion criteria for this research were all Syrian residents aged 18 or older. The questionnaire utilized for this study consisted of three major sections: socio-demographic data, knowledge of stroke, and attitudes and perceptions about stroke.   RESULTS: 53.3 % of the 1,143 research participants were female. Most respondents (94.3%) recognized the brain as the organ impacted by stroke. Hypertension was the stroke's most identifiable cause and risk factor (72.8% and 73.6%, respectively). 72.8 % of participants recognized hypertension and atherosclerosis as causes of stroke. 94.3 % of survey participants accurately identified the oranges impacted by the stroke; however, only 50.1% properly identified the warning symptoms. 61.4 % of participants utilize the Internet as a source of stroke-related information. 22.3% of individuals aged 21 to 30 had identified at least one stroke warning sign. 12.58% of individuals with a high socioeconomic position have shown a solid understanding of stroke risk factors. Females were projected to be 1.55 times more knowledgeable about stroke warning signs than men (P value<0.05). It was expected that participants who believed that stroke is avoidable would be 2.2 times more knowledgeable about stroke warning signals than those who disagreed (P value<0.05). Participants who identified more than four causes of stroke were expected to have 14.77 times more knowledge of stroke risk factors than those who did not (P value<0.05).   Conclusion: Our research shows that although knowledge of stroke risk factors and symptoms is moderate to good, there is still a lack of perceptions toward this disease. Hopefully, this will encourage hospitals and other medical groups to continue their awareness-raising campaigns about the dangers of this illness. Stroke prevention and community response may be greatly enhanced by raising public consciousness of the condition and fostering individual agency in coping with it.